A class of shape-shifting composite metamaterial honeycomb structures with thermally-adaptive Poisson's ratio signs. (15th October 2019) - Lim, Teik-Cheng
Abstract: This paper introduces a class of honeycomb composite metamaterials whereby the increase and decrease in temperature give rise to opposing microstructural geometries in situ, thereby leading to Poisson's ratio of opposing signs. The metamaterial consists of rigid crossbeams from which alternating bimaterials are joined onto. Four types of this class of metamaterial, depending on the relative location of the bimaterial phase with higher coefficient of thermal expansion within each unit cell, have been identified. The O-Type and X-Type metamaterials, in which each unit cell has 2 axes of symmetry, exhibit sign-reversal of Poisson's ratio upon temperature change sign reversal. The CC-Type has one axis of symmetry in each unit cell while the SS-Type possesses a 180-degree rotational symmetry; these metamaterial types display zero Poisson's ratio and zero thermal expansion in a specific direction. This class of metamaterial avails to the practising engineer the possibility of designing materials and structures with in situ sign-switchable Poisson's ratio by means of thermal-toggling, as well as those that require good dimensional stability.